2003
DOI: 10.2527/2003.812432x
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenic enzyme activities in different adipose depots of Pirenaican and Holstein bulls and heifers taking into account adipocyte size

Abstract: The effects of sex, genotype, and adipose depot on lipogenic enzyme activity have been investigated in Holstein and Pirenaican bulls and heifers, taking into account differences in adipocyte size. Fifteen Pirenaican bulls and 15 heifers and 15 Holstein bulls and 13 heifers were fattened until slaughter (12 to 13 mo old and 450 to 500 kg of body weight). During the fattening period, animals had ad libitum access to commercial concentrates and straw. The 10th rib was dissected to determine the fat content. Adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
32
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
7
32
1
1
Order By: Relevance
“…The degree of lipid accumulation was intermediate in the Pirenaica and Parda Alpina breeds, which, together with the Asturiana and Rubia Gallega breeds, are raised principally in northern Spain (Casasú s et al, 2002). A comparison of Pirenaica bulls and Holstein bulls, deemed to be an early-maturing breed, showed that the latter exhibited a higher degree of lipid accumulation than the former (Eguinoa et al, 2003). Mendizabal et al (1999) reported results similar to the findings reported here in bulls of these same seven breeds at an intermediate weight at slaughter of 470 kg BW.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of lipid accumulation was intermediate in the Pirenaica and Parda Alpina breeds, which, together with the Asturiana and Rubia Gallega breeds, are raised principally in northern Spain (Casasú s et al, 2002). A comparison of Pirenaica bulls and Holstein bulls, deemed to be an early-maturing breed, showed that the latter exhibited a higher degree of lipid accumulation than the former (Eguinoa et al, 2003). Mendizabal et al (1999) reported results similar to the findings reported here in bulls of these same seven breeds at an intermediate weight at slaughter of 470 kg BW.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen-month-old steers and heifers have leanto-fat ratios 20% and 45% lower than bulls (Gettys et al, 1988). This may partly result from the greater amount of fat, larger adipocytes and in general greater lipogenic activities in females than in males, both in meat and dairy breeds, compared at similar adiposity (Eguinoa et al, 2003).…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 96%
“…In several studies comparing pure or crossbred Pirenaican, Limousin, Holstein, Wagyu, Santa Gertrudis, Angus, and Japanese Black growing cattle it was repeatedly observed that the leaner breeds had lower adipocyte size in carcass and muscular WAT (Miller et al, 1991;May et al, 1994;Eguinoa et al, 2003), concomitant with lower gene expression of C/EBPs (Yamada et al, 2009) and PPARg (Bonnet et al, 2007), lipogenic activities (Hood and Allen, 1973;Miller et al, 1991;Eguinoa et al, 2003;Bonnet et al, 2007), leptin gene expression (Chilliard et al, 2005;Bonnet et al, 2007), and higher resistin (Komatsu et al, 2005) when slaughtered at similar age. However, when growing animals were slaughtered at different ages, but similar carcass adiposities, no differences between breeds persisted for gene expression of C/EBPs (Xu et al, 2009;Yamada et al, 2009), lipogenic activities (Chakrabarty and Romans, 1972;Eguinoa et al, 2003) or leptin gene expression (Chilliard et al, 2005). This shows that the lower adiposity repeatedly observed in lean genotypes partly results from a delay in adipocyte hypertrophy relative to fatter genotypes, and thus to their lower maturity at any given age or weight.…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
“…The activities of FAS and G6PDH, which are involved in de novo lipogenesis, and G3PDH, which is involved in glycerol phosphate synthesis, strongly decreased from 180 dpc onwards when expressed per million adipocytes or from 210 dpc onwards when expressed per milligram of proteins. Difficulties encountered in establishing a satisfactory and meaningful baseline expression of enzyme activities in AT have been repeatedly reported (Bonnet et al, 2000;Eguinoa et al, 2003;Bonnet et al, 2004). Expressing results on a cellular or protein basis was shown to be more relevant because of its better relation to total activity in the studied AT sites (Hood and Allen, 1973).…”
Section: Discussionmentioning
confidence: 98%